Sponge gourd: A novel plant for bee paradise - Halder, Jaydeep; Chaubey, T; Manimurugan, C; Kumar, R; Singh, P M (Indian Horticulture, 2021)
Sponge gourd (Luffa cylindrica (Linn.)) is a popular cucurbitaceous vegetable of India. Being a cross-pollinated and entomophilous crop, it attracts a large number of arthropod fauna thoroughout its crop growth, especially during its long flowering phase. Insects from 8 orders (Coleoptera, Diptera, Hymenoptera, Hemiptera, Neuroptera, Lepidoptera, Odonata and Orthoptera) comprising parasitoids, predators, pollinators and pests are attracted by its bright yellow coloured flowers. All four honey bee species (Apis cerana indica, A. dorsata, A. florea and A. mellifera) were found to visit its flowers and constituted 50 to 60% of total pollinators. Apart from honey bees, other pollinators like carpenter bee, stingless bee, leaf cutter bee, syrphid fly, moths, butterflies, skipper, fruit fly, etc. were also recorded as visitors to its flowers. During the summer season when a very few crops were available in the region; sponge gourd is one of the flowering plants that provides ample amount pollens and nectars to the pollinators. So, for apiculture and meliponiculture, this popular short duration cucurbitaceous vegetable could be a better option for rearing of bees particularly during the lean period apart from its nutritious fruits as vegetables.